An outbreak and control of dengue fever in Yong'an City， Fujian Province - GUAN Huiri; FAN Guang; CAO Banghong; LI Lili; LYU Ting (Shanghai yufang yixue, 2022)
ObjectiveTo investigate a local outbreak of dengue fever in 2019 in a city village in Yong'an City， determine its characteristics， and evaluate the effect of countermeasures.MethodsEpidemic characteristics of the outbreak were analyzed by descriptive analysis， and the effect of countermeasures was evaluated using the number of new cases and the change in mosquito vector density.ResultsThe density of mosquito vectors in the core areas of the epidemic areas was gradually reduced by implementing multiple countermeasures. The Braitu index decreased below the threshold of dengue fever transmission. After the longest incubation period of the last case， there was no further case of dengue fever. The outbreak ended on 28th November.ConclusionThis is a local outbreak of dengue fever. Comprehensive measures should be implemented to control the epidemic by principally eliminating adult mosquitoes and clearing mosquito breeding grounds， be supplemented by isolation and treatment of cases.